Study on permeability mechanism of rough fractured coal considering slippage effect - Xingyi ZENG; Bobo LI; Jianhua LI; Shulei DUAN; Yunna DING; Junsong YANG (Meitan kexue jishu, 2025)
In order to explore the influence of the surface roughness of coal fractures on the permeability characteristics of coal, coal samples from Liupanshui area of Guizhou Province were selected, and the pore structure of coal was characterized by scanning electron microscopy and low-temperature nitrogen adsorption test, and the surface roughness of coal was preliminarily analyzed by Hurst theory. On this basis, the fractal theory is used to further quantitatively characterize the relative roughness of the fracture surface of coal, and a theoretical model of apparent permeability of coal considering the stress, slippage effect and relative roughness of the fracture surface is established, and the influence of the relative roughness of the fracture surface on the gas slip factor is discussed, which is verified and analyzed by the laboratory test results of the permeability of coal. The results show that: ① SEM test showed that there were rough microelements on the surface of the pore fracture structure, and the results of low-temperature nitrogen adsorption test showed that the pore fracture structure of coal was developed, with fractal characteristics and strong heterogeneity. ② The relative roughness of the surface of coal fractures increases with the increase of the fractal dimension of rough microelements. When the fractal dimension of the rough microelement is constant, the relative roughness of the fracture surface decreases with the increase of the scale proportion ε of the rough microelement, and the smaller the fracture opening b of the coal, the more sensitive the relative roughness of the fracture surface is to the fracture opening. ③ With the increase of the relative roughness of the fracture surface, the slippage effect increases. ④ When the initial slip coefficient is the same, with the increase of pore pressure, the apparent permeability of coal gradually decreases and tends to be flat. The slippage effect promotes the infiltration of coal, and the larger the slippage coefficient, the stronger the effect.